2011
DOI: 10.1002/ejoc.201100104
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Symmetry Versus Desymmetrization for Bicyclo[2.2.2]octenes in the Presence of a Bridgehead Amide Group

Abstract: Keywords: Isomerization / Ionic liquids / Green chemistry / Microwave chemistry / Bicyclic compounds An efficient, microwave-assisted and ionic-liquid-catalyzed esterification of bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride derivatives into the corresponding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We found that such conditions (analogous to those used previously) [31,32] were not adequate to achieve quantitative conversion into the products 5; indeed, the only way to achieve this was to apply higher reaction temperatures (140-180°C). However, in order to reach temperatures above 120°C while keeping the pressure below the upper limit [as the boiling point of the neat ethyl vinyl ether (2) is rather low (33°C)], it was necessary to add some appropriate additives to decrease the vapor pressure, such as ionic liquids (e.g., [bmim]BF 4 ) or n-butanol (which, due to the easier isolation of the products, proved to be preferable) [47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…We found that such conditions (analogous to those used previously) [31,32] were not adequate to achieve quantitative conversion into the products 5; indeed, the only way to achieve this was to apply higher reaction temperatures (140-180°C). However, in order to reach temperatures above 120°C while keeping the pressure below the upper limit [as the boiling point of the neat ethyl vinyl ether (2) is rather low (33°C)], it was necessary to add some appropriate additives to decrease the vapor pressure, such as ionic liquids (e.g., [bmim]BF 4 ) or n-butanol (which, due to the easier isolation of the products, proved to be preferable) [47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…An effective intramolecular hydrogen bonding between the N–H proton and the C-2 carbonyl group to form a 6-membered ring renders the latter more electrophilic and consequently more reactive toward the nucleophiles (Figure ). This has been supported by an independent experiment with the N -methyl derivative 10a , prepared by the methylation of 5a with dimethyl sulfate under basic conditions and shown in Scheme . Under the same hydrolytic reaction conditions as for 5a , the N -methyl derivative 10a afforded a complex mixture of products.…”
mentioning
confidence: 78%
“…55 Base-catalyzed isomerization of these tetraesters 86 takes place with the retention of symmetry and yields the products 87 that are appropriate substrates for catalytic hydrogenation. This hydrogenation proceeds under far milder conditions (5 h at room temperature, 3 bar of H 2 and with standard Pd/C as the catalyst) as were necessary for the above mentioned bicyclo[2.2.2]octenes 82 (analogous to those before the isomerization) indicating that the isomerization (86 → 87) strongly decreases the steric hindrance around the double bond.…”
Section: Scheme 24mentioning
confidence: 99%